3D Chemical Cross‐Linking Structure of Black Phosphorus@CNTs Hybrid as a Promising Anode Material for Lithium Ion Batteries. (31st January 2020) - Zhang, Yupu; Wang, Lili; Xu, Hao; Cao, Junming; Chen, Duo; Han, Wei
Abstract: The existence of rechargeable lithium ion batteries with high operating voltage, high energy density, and excellent cycling performance are drawing increasing attention due to their viability to be used as portable power and in electrical applications. However, there is a considerable problem that the conductivity of the active material becomes poor due to the volume expansion under the condition of repeated circulation, which reduces the performance of the device, thus hindering its practical application. As an emerging 2D material, black phosphorus (BP) has drawn significant attention in the field of Li‐ion battery energy storage due to its large theoretical capacity of 2596 mA h g −1 and ability to absorb large amount of Li atoms. Here, a unique 3D conductive structure with the BP and carbon nanotubes (CNTs), displaying good stability and high conductivity for the fabrication of BP@CNTs hybrid‐based Li‐ion batteries is described. With strong trapping, good affinity, structure stable, and high adsorption for polyphosphorus, the developed BP@CNTs hybrid electrodes display high capacity, good electrical conductivity, and a stable cycle life. Additionally, the lithium ion batteries can illuminate the light emitting diode, proving that the materials have great potential for development of energy storage devices. Abstract : Enhanced electrochemical performance of black phosphorus@carbon nanotubes (BP@CNTs) hybrids‐based lithium ion batteries is achieved by using a new chemical cross‐linking method for self‐assembly of BP on CNTs through van der Waals interactions.